FOXO3 modulates endothelial gene expression and function by classical and alternative mechanisms - Czymai, Tobias; Viemann, Dorothee; Sticht, Carsten; Molema, Grietje; Goebeler, Matthias; Schmidt, Marc (The journal of biological chemistry, 2010)
FOXO transcription factors represent targets of the phosphatidylinositol 3-kinase/protein kinase B survival pathway controlling important biological processes, such as cell cycle progression, apoptosis, vascular remodeling, stress responses, and metabolism. Recent studies suggested the existence of alternative mechanisms of FOXO-dependent gene expression beyond classical binding to a FOXO-responsive DNA-binding element (FRE). Here we analyzed the relative contribution of those mechanisms to vascular function by comparing the transcriptional and cellular responses to conditional activation of FOXO3 and a corresponding FRE-binding mutant in human primary endothelial cells. We demonstrate that FOXO3 controls expression of vascular remodeling genes in an FRE-dependent manner. In contrast, FOXO3-induced cell cycle arrest and apoptosis occurs independently of FRE binding, albeit FRE-dependent gene expression augments the proapoptotic response. These findings are supported by bioinformatical analysis, which revealed a statistical overrepresentation of cell cycle regulators and apoptosis-related genes in the group of co-regulated genes. Molecular analysis of FOXO3-induced endothelial apoptosis excluded modulators of the extrinsic death receptor pathway and demonstrated important roles for the BCL-2 family members BIM and NOXA in this process. Although NOXA essentially contributed to FRE-dependent apoptosis, BIM was effectively induced in the absence of FRE-binding, and small interfering RNA-mediated BIM depletion could rescue apoptosis induced by both FOXO3 mutants. These data suggest BIM as a critical cell type-specific mediator of FOXO3-induced endothelial apoptosis, whereas NOXA functions as an amplifying factor. Our study provides the first comprehensive analysis of alternatively regulated FOXO3 targets in relevant primary cells and underscores the importance of such genes for endothelial function and integrity.